Learning that Students Who Know Themselves in Analysis Geometric - PHOMMANITH, Khamsone; VONGSIPASEUTH, Bounmor; BOUSITH , Oudom; KHONEPACITH , Domone; SAYDUANGTA, Soulinthong (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
The purposes of this research were: [1] to create learning activities by students, [2] to invstigate students' learning achievement in Geometric Analysis, and [3] to find out the attitudes of students towards learning activities that were created by students themselves. The sample is composed of two groups: the first group was teachers who provided basic information and comments at the meeting (4 people), and the second group was students who created learning activities and used for their learning Geometric Analysis course over the academic year 2020-2021 (19 students) using Conveniences Sampling. The instrument used in this research included learning activities, a Geometric Analysis test with a reliability level of 0.8119, and an attitude evaluation form toward learning activities. The statistics for data analysis were the percentage, mean, standard deviation, and t-test. The findings were as follows: Learning activities created by students themselves were effective, with a value of 73.05/72.16, which is higher than the hypothesis value of 70/70, students' learning achievement using earning activities created by students themselves equaled 70 percent, and attitude towards learning activities created by students themselves at the medium level.